Comparative Analysis of Single and Dual Rear Tire Configuration on a Front Wheel Drive Assist Tractor - Hyde, Richard; Dayberry, Thomas; Batey, Andy; Shell, Lon R. (Journal of Agricultural Systems, Technology, and Management, 1988)
N/A